Improving Research Patient Data Repositories From a Health Data Industry Viewpoint - Chunlei Tang; Jing Ma; Li Zhou; Joseph Plasek; Yuqing He; Yun Xiong; Yangyong Zhu; Yajun Huang; David Bates (JMIR Publications, 2022)
Organizational, administrative, and educational challenges in establishing and sustaining biomedical data science infrastructures lead to the inefficient use of Research Patient Data Repositories (RPDRs). The challenges, including but not limited to deployment, sustainability, cost optimization, collaboration, governance, security, rapid response, reliability, stability, scalability, and convenience, restrict each other and may not be naturally alleviated through traditional hardware upgrades or protocol enhancements. This article attempts to borrow data science thinking and practices in the business realm, which we call the data industry viewpoint, to improve RPDRs.